Challenges in organic component selection and biochar as an opportunity in potting substrates: a review. (21st July 2019) - Zulfiqar, Faisal; Allaire, Suzanne E.; Akram, Nudrat Aisha; Méndez, Ana; Younis, Adnan; Peerzada, Arslan Masood; Shaukat, Narmeen; Wright, Shawn R.
Abstract: Plant production in potting substrates provides maximum profit on the applied inputs, and hence, directly improving the socio-economic condition of the grower/nurserymen. The main challenge in this industry is sourcing of materials for their potting substrates. Peat and perlite have been widely preferred materials. However, recently higher prices, more restrictive legislation of many countries and wetland ecosystem destruction through its extraction has limited peat use. Nowadays, producers focus towards peat alternatives that provide good performance, are readily available, inexpensive and environment friendly to attain sustainability in potted plant production. In an effort to grasp sustainability during the last few decades, many industrial and agricultural waste materials were reviewed for their use in potting substrates. In these studies, the major focus remained on material characterization, neglecting their economics, technical aspects and environmental impacts. Thus, switching from peat and perlite to alternatives requires material exploration. In the present review, we summarize a clearer and practical approach for substituting different materials especially biochar to fulfill the need of modern potting substrate industry. Biochar has the potential to sustain the substrate production on a long-term basis.